Use the power you have : a brown woman's guide to politics and political change - Jayapal, Pramila, 1965- (The New Press, 2020)
-- all Written with passion and insight, Use the Power You Have offers a wealth of ideas and inspiration for a new generation of engaged citizens interested in fighting back and making change, whether in Washington or in their own communities.
Keywords: Jayapal, Pramila, -- 1965-; United States. -- Congress. -- House -- Biography.; United States. -- Congress. -- House; Women legislators -- United States -- Biography.; Legislators -- United States -- Biography.; East Indian American women -- Biography.; Women immigrants -- United States -- Biography.; Progressivism (United States politics); United States -- Politics and government -- 1989-; Electronic books.; Femmes parlementaires -- États-Unis -- Biographies.; Parlementaires -- États-Unis -- Biographies.; Américaines d'origine indienne -- Biographies.; Immigrantes -- États-Unis -- Biographies.; Progressisme -- États-Unis.; États-Unis -- Politique et gouvernement -- 1989-; Livres numériques.; e-books.; PHILOSOPHY -- Political.; POLITICAL SCIENCE / Political Process / Political Advocacy; East Indian American women; Legislators; Politics and government; Women immigrants; Women legislators; United States; Since 1989; autobiographies (literary genre); Autobiographies; Biographies; Autobiographies.; Biographies.